Kemampuan Matematis Siswa dalam Menyelesaikan Soal HOTS pada Materi Teorema Pythagoras SMP Kelas VIII - Petra, Petra Krister Isolaka (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study was to analyze students' mathematical abilities in solving HOTS problems on the Pythagorean theorem material for eighth grade junior high school students. The type of research used in this study is descriptive qualitative. The subjects of this study were 20 students. The data collection tool was a HOTS question sheet consisting of 30 multiple-choice questions, each consisting of 10 questions at each level starting from C4, C5, and C6. The data analysis technique used descriptive analysis of student test results. The results of this study concluded that students' mathematical abilities in working on HOTS problems on the Pythagorean theorem material were still very low. This can be seen from the average student score of 44.67. From these results, it is known that 13 students have very low abilities, 4 students have low abilities, 2 students have medium abilities, 1 student has high abilities, and 0 students have very high abilities. Of the three levels of HOTS questions, 50% of students answered correctly at the C4 level, 44% of students answered correctly at the C5 level, and 40% of students answered correctly at the C6 level.